Mindfulness interventions for rheumatoid arthritis: A systematic review and meta-analysis. (May 2020) - Zhou, Bo; Wang, Gang; Hong, Yin; Xu, Shan; Wang, Jialong; Yu, Hejun; Liu, Yun; Yu, Liang
Abstract: Objectives: To explore the effect of mindfulness interventions in improving outcomes for patients with rheumatoid arthritis. Methods: Following the collective strategy of Cochrane Collaborative Group, the Cochrane Library, PubMed, EMBASE, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, and Wanfang Database were searched from the establishment of databases to September 2019. Reference lists were searched for additional studies. Risk of bias was assessed using Revman 5.3. Disagreement was resolved by discussion. Results: A total of 6 RCTs were included, including 337 patients. The results showed that the improvement of pain intensity in mindfulness group after intervention was better than that in the control group, and the difference was significant [WMD = 0.65, 95% CI (−1.11, - 0.18), P = 0.006]. There were significant differences in depression between the two groups [SMD = 0.47, 95% CI (- 0.86, - 0.07), P = 0.02]. The results showed that there were significant differences in DSA28 between the two groups [WMD = −0.29, 95% CI (- 0.38, - 0.19), P ＜0.00001]. The results showed that there were no significant differences in anxiety and CPR between the two groups. Conclusion: mindfulness interventions can significantly improve pain intensity, depression, and symptoms in patients with rheumatoid arthritis compared with conventional therapy. But the result still needs to be confirmed by more high-quality, large-sample randomized controlled trials. Highlights: Mindfulness interventions, as a complementary therapies in clinical practice, can significantly improve pain intensity, depression, and symptoms in patients with rheumatoid arthritis. Adverse effects accompanying the use of mindfulness interventions were not pinpointed in all the studies. We suggests that we need to make full use of the Internet to link the mindfulness interventions line (in hospital) and online (outside the hospital), such as developing mindfulness meditation App, orienting courses and online psychological counseling.